Comparison of Caudal Block and Nalbuphine for Pain Management in Children - Naeem Liaqat , Khursheed Anwar, (Journal of Rawalpindi Medical College, 2016)
Background: To compare pain scores in patients undergoing inguinal herniotomy after caudal block and intravenous nalbuphine. Methods: In this randomized controlled trial a total of 100 patients of age 4-12 years undergoing inguinal herniotomy were included. They were divided into two groups (50 patients in each group); Group A included Caudal block and Group B included patients who received Nalbuphine. Patients in group A were given caudal block while in group B were given nalbuphine 0.1-0.3mg/kg. Pain scores were calculated at 0,1,2,4 and 8 hours. Requirement for rescue analgesia was calculated. All the data were analyzed by SPSS version 16. Results: The mean age of patients were found as 4.15 ± 3.32 years in group A and 4.88 ± 3.18 years in group B. All the other demographics were comparable in both groups. The mean pain scores were less in nalbuphine group at 0,1,2 and 4 hours, however it was significant at 0 and 1 hour. The requirement of rescue analgesia was less in group B than group A (14% vs 34%, p <0.05). The only side effect was observed was vomiting in 12% of patients in group B while in none of patient in group A. Conclusion: Nalbuphine is better than caudal block for pain management in children undergoing inguinal herniotomy.